Figurative Language in White Swan’s Song Lyrics - Ni Putu Erika Amanda Putri Pande; I Wayan Budiarta; I Gusti Ngurah Adi Rajistha (PRAGMATICA : Journal of Linguistics and Literature, 2023)
The title of this research is Figurative Language in ‘White Swan’s Song Lyrics.’ This research aimed to discuss and solve the problems. The problems were conducted into two scopes of discussion. Therefore, the research discussed types of figurative language and the function of figurative language. The data were collected by listening and watching the music video on YouTube. Based on the theory Sound and Sense: An Introduction to Poetry by Perrine (1987), the findings were implied. After analyzing the data, the finding was 62 frequency of figurative language that has been shown. In terms of the types, they were 7 findings of simile, 31 findings of metaphor, 5 findings of personification, 4 findings of apostrophe, 1 finding of synecdoche, 3 findings of metonymy, 6 findings of symbolism, 1 finding of paradox, 4 findings of hyperbole.